PERAN KINERJA PEGAWAI DALAM MENINGKATKAN KUALITAS PELAYANAN PUBLIK DAN KEPUASAN MASYARAKAT: Penelitian Survey pada Desa Pasirmuncang Kecamatan Panyingkiran Kabupaten Majalengka, Jawa Barat - Widia; Kania Agustina (Universitas Majalengka, 2021)
This study aims to analyze descriptively about the performance of the apparatus, the quality of public services and community satisfaction. This study uses descriptive analysis with the average value which is the main guide in this study. This research method uses survey research methods which are carried out on research samples from the results of calculations through the slovin formula and the sampling system is carried out in regional clusters which are divided into Rukun Tetangga. The number of samples determined in this study was 305 people who were proportionally divided into 18 Rukun Tetangga. The results of the study found that the performance of the apparatus, the quality of public services and the satisfaction of the community in the research area had good results, however, there were still some obstacles faced, especially in the mastery of information technology by village government officials in providing electronic-based services to the community